Analisis Kinerja Struktur Atas Gedung 7 lantai Dengan Variasi Dimensi dan Lokasi Shearwall Studi Kasus Konsep Kondominium Hotel - Muhammad Ismail (Jurnal Teknik Sipil dan Lingkungan, 2014)
The final project consists of modifications condominium building with a wide range of alternatives. Condominium hotel is that every hotel room or unit can be owned and traded by individuals. Condominium which has been called the apartment can be operated like a tourist accommodation. A wide variety of alternative building contains about modification alternatives A condominium hotel is an existing building of condominium hotels, alternative B uses modified by adding shearwall angle on the corner of the building, alternative C using shearwall modified by adding "+" between the two buildings, alternative D using a modification by adding shearwall along the edge of the building. After modification condominium building with using a variation of the position and shape of each shearwall on its modeling. Then compare the force of the moment, shear, axial, volume, and deflection or deviation that occurs in each of the modeling. So it can be concluded that modeling is not modified or modeling existing buildings that use Frame System bearer Ordinary Moment (SRPMB) have a smaller volume compared to other modeling using Shearwall or Special Moment Frame Systems bearer(SRPMK). If viewedÂ  from Â the deviation or deflection, the higher floors of building has the greater deflection or deviation. Keyword : Building, Structure,Condominium, Shearwall